Feed Management and Nutritional Status of Gibbons (Symphalangus Syndactylus Raffles, 1821) at Tegal Alur Animal Rescue Center, Jakarta - Fahma Wijayanti; Abdul Bagas Al katiri; Nurul Handayani; Narti Fitriana (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2023)
AbstractGibbon (Symphalangus syndactylus Raffles, 1821) is an endangered species of black long-armed ape that is protected by national and international regulations. This study aims to analyze feeding behavior, feed management and nutritional status of gibbons in Tegal Alur Animal Rescue Center. The study was conducted in March-July 2020, using focal animal sampling and ad libitum sampling methods to 6 individual gibbons. Food management data collection includes information on feeding and the amount of feed, while nutritional status includes physical characteristics of the body, anthropometry, and analysis of feed composition. The results showed that the feeding schedule for gibbons was in accordance with the feeding times of gibbons in nature. Tegal Alur PPS provides food in the form of nine types of fruit, two types of vegetables and one type of leaves. Gibbons at Tegal Alur PPS Alur Animal Rescue Center has met the amount of feed consumption according to body weight. The nutritional status based on anthropometry shows that the body weight of the gibbon is not in accordance with its natural habitat. Morphological observations showed that the gibbon’s teeth and eyes were healthy, while some gibbons had hair loss and depigmentation.AbstrakOwa (Symphalangus syndactylus Raffles, 1821) merupakan spesies kera hitam lengan panjang yang terancam punah dan dilindungi oleh peraturan nasional dan internasional. Penelitian bertujuan untuk menganalisis perilaku makan, pengelolaan pakan, dan status gizi owa di Pusat Penyelamatan Satwa (PPS) Tegal Alur. Penelitian dilakukan pada bulan Maret-Juli 2020, dengan metode focal animal sampling dan ad libitum sampling pada 6 individu owa. Pendataan pengelolaan pakan meliputi informasi pakan dan jumlah pakan, sedangkan status gizi meliputi ciri fisik tubuh, antropometri, dan analisis komposisi pakan. Hasil penelitian menunjukkan bahwa jadwal pemberian pakan owa sesuai dengan waktu pemberian pakan owa di alam. PPS Tegal Alur menyediakan makanan berupa sembilan jenis buah, dua jenis sayuran dan satu jenis daun-daunan. Owa di Pusat Penyelamatan Satwa Tegal Alur telah memenuhi jumlah konsumsi pakan sesuai dengan berat badan. Status gizi berdasarkan antropometri menunjukkan bahwa berat badan owa lebih rendah dengan berat badan Owa di habitat aslinya. Pengamatan morfologi menunjukkan bahwa gigi dan mata owa dalam keadaan sehat, sementara beberapa owa mengalami kerontokan rambut dan depigmentasi.